Recovery of Calcium Carbonate from Pre-Treated Duck Eggshell Waste (PDEW) Using Dissolved Air Flotation Technique (DAFT) - Nurdin, Said; K. Wei, Lim; V. Sivaguru, Malar; Ibrahim, Nurhamizah; A. Khairuddin, Syafiqah; Athirah M.Sukri, Hajar (International Journal of Engineering and Technology, 2018)
Duck eggshell containing rich calcium carbonate was disposed to land fill under economical values application. Effective utilization of Pre-Treated Duck Eggshell Waste (PDEW) may replace calcium carbonate mined from non-renewable sources and chemicals precipitation. The present work evaluates the potential of calcium carbonate recovery from PDEW using Dissolved Air Flotation Technique (DAFT). Operation parameter effects and optimization of PDEW membrane segregation were also investigated. The collected duck eggshell was cleaned in tap water, dried in hot air oven and ground to small pieces. Separation vessel was used for organic membrane partition by various air pressure, eggshell to water ratio and residence time. Characterization of PDEW before and after treatment was carried out using Thermogravimetric Analysis (TGA), Scanning Electron Microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR). The DAFT has successfully recovered 92.5% duck eggshell calcium carbonate, and 60% of eggshell organic membrane removed. Removal rate of duck eggshell membrane was found at optimal condition of 1.62 bar air pressure, eggshell to water ratio of 1:5.68 and 1.41 h of residence time. The DAFT and PDEW spread marvelous results of calcium carbonate recuperation, and it can be ruminated on future technique and carbonate derivation.Â Â